Spin evolution of Earth-sized exoplanets, including atmospheric tides and core–mantle friction. Issue 2 (April 2015) - Cunha, Diana; Correia, Alexandre C.M.; Laskar, Jacques
Abstract Planets with masses between 0.1 and 10 M⊕ are believed to host dense atmospheres. These atmospheres can play an important role on the planet's spin evolution, since thermal atmospheric tides, driven by the host star, may counterbalance gravitational tides. In this work, we study the long-term spin evolution of Earth-sized exoplanets. We generalize previous works by including the effect of eccentric orbits and obliquity. We show that under the effect of tides and core–mantle friction, the obliquity of the planets evolves either to 0° or 180°. The rotation of these planets is also expected to evolve into a very restricted number of equilibrium configurations. In general, none of these equilibria is synchronous with the orbital mean motion. The role of thermal atmospheric tides becomes more important for Earth-sized planets in the habitable zones of their systems; so they cannot be neglected when we search for their potential habitability.